Perception of undergraduate nursing students’ toward their future professional career - Hailu, Leta Dammene; Ilala, Birhanu Wogane; Germossa, Gugsa Nemera (Frontiers in Education, 2025)
ObjectivesTo assess the perception of undergraduate nursing students toward their future nursing careers at Jimma University, Southwest Ethiopia, 2023.MethodologyA cross-sectional study was carried out among undergraduate nursing students at Jimma University from 1 to 30 November, 2023. Data was collected using a self-administered questionnaire from 200 undergraduate nursing students. The collected data was then entered directly into SPSS version 26 for analysis. Subsequently, descriptive analysis was performed, and the findings were presented in the form of text, and tables.ResultOut of the 207 undergraduate nursing students, 200 undergraduate nursing students responded accordingly, resulting in a 96.6% response rate. Findings show that 83.5% of nursing students view nursing as dignified and respectful, 71% perceive it as equal to other professions, and 89.5% acknowledge its role in serving humanity. Additionally, 55% believe the profession offers personal growth opportunities, and 93% perceive nursing as a caring profession with strong ethical standards. Furthermore, 88.5% of students plan to go abroad, and 80% express a desire for further educational opportunities.ConclusionThis study showed that nursing students at Jimma University generally hold favorable views of nursing and are driven by altruistic values, concerns about the demanding nature of the profession, under appreciation, and the desire to go abroad. These findings reflect broader global trends in the nursing workforce. Addressing these challenges through supportive educational programs and improved working conditions will be critical for ensuring the long-term sustainability of the nursing profession, particularly in countries like Ethiopia, where healthcare workers are in high demand.